Pengaruh Pendidikan Kesehatan Dengan Metode Buzz Group Terhadap Perilaku Ibu Tentang Pencegahan Pneumonia Pada Balita - Yanti, Lindesi; Mahchmud, Rizanda; Fajriah, Lili (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2021)
Pneumonia is the second leading cause ofdeath after diarrhea in Indonesia. Health education is an effort toincrease knowledge, attitudes, and actions in the prevention ofpneumonia. Buzz group one method ofhealtheducation can stimulate the active role ofmothers in expressing opinions about pneumonia prevention. Thepurpose ofthe study was to determine the effect ofbuzz group health education on maternal behavior. Thistype of quantitative research with Non-Equivalent Control Group design. The number of samples was 76people, with the technique ofSimple Random Sampling. The Independent Samples T-test shows differencesin knowledge, attitudes, and actions in the intervention and control groups. The MANOVA test showed thatthe buzz group method was most influential in increasing knowledge, attitudes, and actions (p <α = 0.05).Conclusion The Health education method of the buzz group is more effective in increasing knowledge,attitudes, and actions of mothers regarding the prevention of pneumonia in infants compared to lecturemethods. Suggestions for Puskesmas to conduct health education using the buzz group method as an effectivemethod as a promotional and preventive effort.